2019
DOI: 10.4034/pboci.2019.191.120
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemography, Oral Health Status and Behaviours Related to Oral Health Literacy

Abstract: Objective: To assess the relationships of socio-demography, self-reported oral health status, and behaviour with oral health literacy (OHL) among adults. Material and Methods: A crosssectional study was conducted during a mega carnival in Kuala Lumpur. Socio-demographic, oral health status, and oral health behaviour data were obtained using a questionnaire, and OHL was determined by a validated Malay version of the 14 items Health Literacy in Dentistry Scale (HeLD-14). A total of 165 data of participating adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
(41 reference statements)
3
10
0
Order By: Relevance
“…The employment status (0.00 *) of the parents showed a significant relation with the OHL level. This agrees with a study conducted by Noor et al [ 42 ], wherein the authors revealed that 20% of the Malaysian population had significantly higher OHL scores when compared with different income categories. The literature has revealed that the employment status of the parents plays a significant role in improved OHL [ 64 , 66 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The employment status (0.00 *) of the parents showed a significant relation with the OHL level. This agrees with a study conducted by Noor et al [ 42 ], wherein the authors revealed that 20% of the Malaysian population had significantly higher OHL scores when compared with different income categories. The literature has revealed that the employment status of the parents plays a significant role in improved OHL [ 64 , 66 ].…”
Section: Discussionsupporting
confidence: 92%
“…Childhood oral health depends on the awareness of their parents, as the OHL of parents affects the oral health-associated lifestyles of children, which are developed during the initial stages of childhood and continue in later stages [ 39 , 40 , 41 ]. The prevalence of caries among the Malaysian adult population was reported as 88.9% according to the National Oral Health Survey of Adults in Malaysia [ 42 ]. According to the Malaysian ministry of health, the prevalence of dental caries among preschool children was reported to be 71.3% [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to the development of the Malaysian adaptation of the HLS-EU-Q47, health literacy in Malaysia was assessed utilising different instruments ranging from the Newest Vital Signs [35] to tools addressing specific disease literacy such as in dentistry [36,37] and in mental health [38]. The HLS-M-Q18 has enabled the measurement of health literacy in line with current global standards.…”
Section: Discussionmentioning
confidence: 99%